Records of the Colony and Plantation of New Haven: From 1638 To 1649, at 96-97 (Charles J. Hoadly ed., 1857) (enacted 1643) - (:unkn) unknown (My University, 1643)
Itt is ordered thatt every male, fr? 16 yeares olde to sixty, wthin this jurisdict?, shall be forthwth furnished of a good gun or muskett, a pound of good pouder,4 fathom of match 97 for a match-lock, and 5 or 6 good flints, fitted for every fyre lock, and 4 pound of pistoll bulletts, or 24 bulletts fitted to their guns, and so continue furnished fromtime to time,vnder the penalty of 10s fine vpon every defect in any of the forenamed perticulars
Keywords: REQUIRED POSSESSION